Educommunication and Artificial Intelligence: Guide to a Conversation in Times of Digital Unrest Páginas - Karam Cárdenas, Tanius (2025)
In this paper, we situate the phenomenon of Artificial Intelligence (AI) within the context of Education 4.0, outlining some of its key  elements. We propose an educommunicative approach, which not only examines the technological implications of AI but also  considers educommunicative actors, messages, and the cultural environment. To this end, we draw on the Pedagogy of Total Language, which allows us to redefine certain general communication objectives and promote a new attitude among  educommunicative actors based on the conversational lines proposed in this study. In this regard, we consider it essential to  incorporate mediological and ecological perspectives, which have proven useful in rethinking the implications of technological  transformations. This paper presents a conversation guide structured into several sections: 1. identification of similarities and  differences between the various media-spheres across different stages of technological change (defined as Education 1.0, 2.0, etc.);  2. enumeration of key components of AI, aiming to clarify what it is and what it is not; 3. revisiting the debate between “apocalyptic”  and “integrated” perspectives by offering an initial list of AI-related opportunities and challenges; and 4. formulating questions and  discussions that help structure the levels of abstraction at which AI can be analyzed, with a particular focus on educommunicative  actors.